A study of compliment responses of Malaysian Chinese Undergraduates / Wu Yingqi - Wu, Yingqi (2017)
The purpose of this study is to investigate compliment responses (CRs) produced by Malaysian Chinese undergraduates and identify the face-saving strategies applied in their compliment responses. The data of this study was collected from 30 Malaysian Chinese undergraduate students in University of Malaya. Role-play scenarios consisted of 8 situations that were recorded and transcribed to investigate the compliment response strategies using Dongmei Cheng’s (2011) framework and Gu’s (1992) politeness framework was used to investigate the face-saving strategies in the compliment responses. The findings show that Malaysian Chinese undergraduates tend to use Acceptance strategy at the macro level. At the micro level, the most preferable strategy appears to be that of Acceptance, especially Appreciation which shows gratitude to the complimenter. On the contrary, Rejection and Offering have been the most unfavorable CRs strategies. Malaysian Chinese undergraduates in arts majors showed a preference of applying Combination strategies compared to the undergraduates in science who preferred Acceptance strategies. The findings of micro CRs strategies revealed that there were no marked distinctions between participants in the two study fields. Social distance and social power affected the choices of CRs. Malaysian Chinese undergraduates in this study were primarily motivated by Gu Yueguo’s Accordance Maxim then Refinement Maxim in their CRs. Findings also reveal that there are some similarities and differences between the Malaysian Chinese in arts and science majors in preference of CRs strategies.